Application of nanoindentation technology for characterizing the mechanical properties of shale before and after supercritical CO2 fluid treatment. Issue 37 (April 2020) - Shi, Xian; Jiang, Shu; Wang, Zhixuan; Bai, Bing; Xiao, Dianshi; Tang, Mingming
Highlights: Nanoindentation method was applied for evaluating mechanical properties for SC-CO2 treated shale. Samples treated by SC-CO2 present lower Hardness, Young's modulus and fracture toughness. We compared nanoindentation results for clay rich and quartz rich area after SC-CO2 treatment. The mechanical properties decrease in clay-rich regions is primarily CO2 adsorption. Abstract: To better implement super critical carbon dioxide (SC-CO2 ) fracturing on shale, it is important to investigate effects of SC-CO2 on rock mechanical properties. Because micro-scale mechanical properties determine the overall mechanical response, the determination of micro-scale mechanical properties is necessary. In this paper, continuous stiffness measurement (CSM) and constant loading rate (CLR) mode nanoindentation was performed on shale samples before and after SC-CO2 treatment. With the aid of scanning electron microscope and energy dispersive spectra mapping technique, mechanical strength difference on clay-rich and quartz –rich areas in shale sample can be identified. The results demonstrated that samples treated by SC-CO2 present lower Hardness, Young's modulus and fracture toughness. The average decrease rates of hardness and Young's modulus under CSM mode for three sample are 32.01 % and 11.75 %. The hardness, Young's modulus and fracture toughness under CLR mode for the three samples have decreased at average rates of 29.5 %, 11.0 %, and 11.3 %, respectively. Moreover, the mechanical strength substantially decreases in the clay-rich area because CO2 adsorption and mineral dissolution happen after the SC-CO2 treatment. The change in mechanical properties in quartz-rich area is much smaller because there is little effect on quartz. The close examination of indentation fracture geometry indicate more micro fractures have been generated in the post SC-CO2 treated shale, thus we can expect the capability of SC-CO2 for rock weaken. This study can provide more insights for fracture mechanism in target areas with different mineral distribution, which is beneficial for SC-CO2 engineering applications.